- HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN FREKUENSI KEJADIAN ISPA PADA BAYI 6-12 BULAN DI WILAYAH KERJA PUSKESMAS NGADILUWIH - Mika Mediawati Mika (JURNAL KEBIDANAN, 2020)
ASI (Mother's Milk) is the best food for babies from the age of 0 months to 2 years. ASI contains the right nutrients according to the needs of the baby. The composition of breast milk that we do not find in formula milk is an immune or antibody substance. Antibodies will provide protection against some bacteria, one of which is the bacteria that causes ARI (Acute Respiratory Tract Infection). The purpose of this study was to determine the long association of jbreastfeeding against the frequency of occurrence of acute respiratory tract infections (ARI) in infants 6-12 months. The approach to be used in this study is an observational (cross sectional and retrospective) research approach. The sample used in this study was mothers who had toddlers aged 1-1.5 years who came to the posyandu in the working area of the Ngadiluwih health center. The analysis test used is the Spearman Rank correlation test. The results of the study using the Spearman Rank analysis test obtained a significance value (P value) 0.028 <0.05, this means that there is a significant relationship between exclusive breastfeeding and the frequency of ARI in infants aged 0 -12 months, while the correlation coefficient (r) -1,27 negative sign indicates a unidirectional correlation, which means that mothers with exclusive breastfeeding will have babies who experience ARI with less frequency, and vice versa, mothers with no breastfeeding exclusive then the frequency of babies suffering from ARI will be more frequent. Things that can trigger the occurrence of various ARIs, exclusive breastfeeding may be one of our efforts to reduce the frequency of ARI in our baby.